2009
DOI: 10.1007/bf03085610
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotica bij exacerbaties van COPD lijkt recidieven te voorkomen

Abstract: InleidingDe pijler van de behandeling van exacerbaties bij COPD (chronic obstructive pulmonary disease) bestaat uit corticosteroïden en antibiotica. Het gebruik van corticosteroïden is goed geaccepteerd, over de rol van antibiotica bestaat veel discussie. Aangenomen wordt dat antibiotica zinvol zijn voor patiënten met ernstige exacerbaties, gekenmerkt door ernstige symptomen, en/ of patiënten met een slechte longfunctiewaarde. 1-3 Een recente Cochrane-review laat zien dat antibioticagebruik op de korte termijn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that readmission within 30 days after discharge in AECOPD patients is related to sex, lung function, systemic glucocorticoid use, Charlson comorbidity index, and quality of medical care (Jo et al, 2020;Yılmaz et al, 2021). Previous studies have shown that antibiotic treatment for AECOPD can significantly prolong the time interval until the next deterioration event (Roede et al, 2008;Roede et al, 2009). Previous studies have also shown that the length of hospital stay can reflect the severity of an AECOPD event (Rinne et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that readmission within 30 days after discharge in AECOPD patients is related to sex, lung function, systemic glucocorticoid use, Charlson comorbidity index, and quality of medical care (Jo et al, 2020;Yılmaz et al, 2021). Previous studies have shown that antibiotic treatment for AECOPD can significantly prolong the time interval until the next deterioration event (Roede et al, 2008;Roede et al, 2009). Previous studies have also shown that the length of hospital stay can reflect the severity of an AECOPD event (Rinne et al, 2017).…”
Section: Discussionmentioning
confidence: 99%